Wireless electrochemical fabrication of tungsten oxide nanoporous layers in closed bipolar cells - Marcela Sepúlveda; Kaushik Baishya; Jhonatan Rodriguez-Pereira; Veronika Cicmancova; Ludek Hromadko; Jan M. Macak (Electrochemistry Communications)
In this work, the anodization of tungsten (W) foils using closed bipolar electrochemical cells is demonstrated for the first time. The anodization was done using three different electrolytes: (1) 1 M NH4NO3, 1 wt%. H2O in ethylene glycol (EG); (2) 1 M (NH4)2SO4, 75 mM NH4F in H2O; and (3) 170 mM NH4 1.5 wt%. H2O in EG. Different square-wave potentials and frequencies were applied during the anodization. Among the tested electrolytes, electrolyte 1 produced the most well-defined and homogeneous WO3 nanoporous (NP) layers. X-ray photoelectron spectroscopy confirmed the presence of multiple W oxidation states on the WO3 NP layers using electrolytes 1 and 2, with W6+ and W5+ being the dominant species. The results demonstrate well-defined WO3 NP layers with a high W6+ species concentration and less than 10 at.% W5+ is achieved using electrolyte 1. These findings provide valuable insights into the relationship between the electrolyte composition, W oxidation states, and the morphology of WO3 NP layers.